Four-Dimensional Printing of β-Tricalcium Phosphate-Modified Shape Memory Polymers for Bone Scaffolds in Osteochondral Regeneration - Rajzer, Izabella; Kurowska, Anna; Janusz, Jarosław; Maślanka, Maksymilian; Jabłoński, Adam; Szczygieł, Piotr; Fabia, Janusz; Novotný, Roman; Piekarczyk, Wojciech; Ziąbka, Magdalena; Frankova, Jana (Materials (Basel, Switzerland), 2025)
The use of scaffolds for osteochondral tissue regeneration requires an appropriate selection of materials and manufacturing techniques that provide the basis for supporting both cartilage and bone tissue formation. As scaffolds are designed to replicate a part of the replaced tissue and ensure cell growth and differentiation, implantable materials have to meet various biological requirements, e.g., biocompatibility, biodegradability, and mechanical properties. Osteoconductive materials such as tricalcium phosphate ceramics and some biodegradable polymers appear to be a perfect choice. The present work evaluates the structural, mechanical, thermal, and functional properties of a shape memory terpolymer modified with β-tricalcium phosphate (β-TCP). A new approach is using the developed materials for 4D printing, with a particular focus on its applicability in manufacturing medical implants. In this study, the manufacturing parameters of the scaffold components were developed. The scaffolds were examined via scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS), Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and mechanical testing. The cytotoxicity result was obtained with an MTT assay, and the alkaline phosphatase (ALP) activity was measured. The structural and microstructural investigations confirmed the integration of β-TCP into the filament matrix and scaffolds. Thermal stability was enhanced as β-TCP delayed depolymerization of the polymer matrix. The shape memory studies demonstrated effective recovery. The in vitro cell culture studies revealed the significantly increased cell viability and alkaline phosphatase (ALP) activity of the β-TCP-modified terpolymer after 3 weeks. The developed terpolymer can be tailored for applications in which partial shape recovery is acceptable, such as bone scaffolds.
Keywords: 4D printing; bone tissue engineering; shape memory polymers; scaffolds